Manufacture of Activated Carbon Adsorbents from Jackfruit Waste for Removal of Heavy Metals and Dyes from Wastewater: A Review - Hong Tham Thi Nguyen; Huong Tra Do; Kim Ngan Thi Tran; Bich Ngoc Hoang; Kim Oanh Thi Nguyen; Sy Chi Phung; Cam Quyen Thi Ngo (Indonesian Journal of Chemistry, 2021)
: Jackfruit is a fruit tree species distributed mainly in Southeast Asia and Brazil. The pulp and skin of jackfruit are widely used in various fields such as food, medicine, and interior decoration. However, the jackfruit processing into edible and usable products generates a large quantity of agricultural waste. In this review, we focused on summarizing the environmental applications of jackfruit waste in wastewater treatment. Specifically, the potential and application of activated carbon synthesized from jackfruit waste were assessed concerning the adsorption of organic dyes and metals from wastewater. In practical water treatment applications, the adsorption kinetic and isothermal models have been evaluated for activated carbon's suitability and adsorption capacity. This study acts as the basis for further development of the by-product materials to environmental treatment application and to reduce the negative impact of agricultural by-products on the environment.